Post-functionalization of a photoactive hybrid polyoxotungstate - Cameron, Jamie M.; Fujimoto, Satomi; Wei, Rong-Jia; Newton, Graham N.; Oshio, Hiroki (Royal Society of Chemistry, 2018)
A new post-functionalization strategy for hybrid polyoxometalate (POM) clusters is presented, whereby the electronic properties and visible-light driven oxidative reactivity of the POM core can be altered by controlled addition of transition metal ions. The structure of three new metal-functionalised derivatives of a phosphonate hybrid-POM are discussed, alongside a comparison of their electrochemical, photo-chemical and photo-oxidative properties.